KAJI NUMERIK PENGARUH CACAT RETAK MELINTANG PADA POROS TERHADAP PERILAKU DINAMIK SISTEM POROS ROTOR - Budiwantoro, Bagus; Kurdi, Ojo; Nugraha, Kurnia (Mesin, 2001)
The stiffness of a cracked shaft changes due to the position of the crack. The problem is how to make a general equation of motion that can be used for all crack positions, so frequency response resulted represents the real frequency response of the cracked shaft. The cracked shaft modelling uses the moment inertia of cracked shaft at various crack positions is the first step. The second step is determining frequency response of significant crack position. The third step is determining the equivalent moment inertia of a cracked shaft that represents the condition of the crack. Next, by using Rayleight-Ritz Method and equivalent moment inertia of cracked shaft, the equation of motion that represents condition of cracked shaft can be determined. The results of this equation are Campbell Diagram and response to force excitation due to mass unbalance and asynchronous force. Dynamic behaviors of system are presented for three positions of crack, namely 0o, 90o, and average position. 0o position is the significant position, 90o position gives the smallest change to dynamic behavior of cracked shaft and the average position represents the condition of the cracked shaft.